2018
DOI: 10.1093/ckj/sfy095
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and chronic kidney disease progression—the role of a new adipocytokine: C1q/tumour necrosis factor-related protein-1

Abstract: Background Obesity is a risk factor for incident chronic kidney disease (CKD) in the general population. C1q/tumour necrosis factor-related protein 1 (CTRP1) is a new adipokine with multiple vascular and metabolic effects and may modulate the association between obesity and vascular diseases. The aim of the study is to explore potential links between obesity, CTRP1 levels and CKD progression. Methods Patients with Stages 3 and 4 CKD without previous cardiovascular event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 41 publications
2
14
0
Order By: Relevance
“…For instance, CTRP1 forms an oligo‐heterotrimer with CTRP6, and is known to enhance glucose uptake and insulin sensitivity . Elevated levels of CTRP1 have been associated with BMI, T2DM, nonalcoholic fatty liver disease (NAFLD), congestive heart failure (CHF), and chronic kidney disease progression . CTRP3, also known as cartonectin, regulates glucose homeostasis and exhibits anti‐inflammatory immunomodulatory role .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, CTRP1 forms an oligo‐heterotrimer with CTRP6, and is known to enhance glucose uptake and insulin sensitivity . Elevated levels of CTRP1 have been associated with BMI, T2DM, nonalcoholic fatty liver disease (NAFLD), congestive heart failure (CHF), and chronic kidney disease progression . CTRP3, also known as cartonectin, regulates glucose homeostasis and exhibits anti‐inflammatory immunomodulatory role .…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation regarding elevation of CTRP1 concentrations in T2D patients might be a self-protective or compensatory mechanism in response to abnormal glucose metabolism. Inconsistent with the above results, it was reported that CTRP1 levels did not significantly higher in diabetic subjects (33). The main reason for this discrepancy could be due to different samples as human and animal models (DIO or ob/ob mice) investigated.…”
Section: Discussionmentioning
confidence: 64%
“…One possible explanation regarding the elevation of CTRP1 concentrations in T2D patients might be a self-protective or compensatory mechanism in response to abnormal glucose metabolism. Inconsistent with the above results, it was reported that CTRP1 levels did not significantly higher in diabetic subjects (33). The main reason for this discrepancy could be due to different samples as human and animal models (DIO or ob/ob mice) investigated.…”
Section: Discussionmentioning
confidence: 64%